2018
DOI: 10.1111/bcp.13519
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of pharmacokinetic interactions between the HCV protease inhibitor simeprevir and frequently used concomitant medications

Abstract: AimsDirect‐acting antiviral agents (DAAs) for the treatment of hepatitis C (HCV) can be associated with drug–drug interactions (DDIs) with concomitant medications. The practical clinical implications of such DDIs are poorly understood. We assessed the clinical impact of possible pharmacokinetic (PK) interactions between simeprevir and frequently prescribed concomitant medications.MethodsThis post hoc analysis pooled data from nine studies which evaluated simeprevir (SMV)‐based interferon‐free HCV treatment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Furthermore, since pDAAs are recommended to the entire HCV population, the diversity of HCV patients eligible to such treatments is expected to increase over the years in terms of age, co–morbidity profile, and polypharmacy regimens [ 6 ]. Clinical trials that investigated the DDI between DAAs and some key drugs generally included patients with limited concomitant medications [ 11 , 12 ]; however, in real life clinical practice, the presence of polypharmacology regimens can make the HCV treatment more challenging than expected [ 13 , 14 , 15 ]. Indeed, studies performed in real-world settings observed among HCV patients high rates of comorbidities and the use of concomitant medication, especially in older ones, which means a greater exposure to potential DDI; moreover, the most commonly concomitant drugs were reported to belong to cardiovascular and central nervous system classes [ 6 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since pDAAs are recommended to the entire HCV population, the diversity of HCV patients eligible to such treatments is expected to increase over the years in terms of age, co–morbidity profile, and polypharmacy regimens [ 6 ]. Clinical trials that investigated the DDI between DAAs and some key drugs generally included patients with limited concomitant medications [ 11 , 12 ]; however, in real life clinical practice, the presence of polypharmacology regimens can make the HCV treatment more challenging than expected [ 13 , 14 , 15 ]. Indeed, studies performed in real-world settings observed among HCV patients high rates of comorbidities and the use of concomitant medication, especially in older ones, which means a greater exposure to potential DDI; moreover, the most commonly concomitant drugs were reported to belong to cardiovascular and central nervous system classes [ 6 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%